Erythromelalgia: An Uncommon Presentation Precipitated by Aspirin Withdrawal. (16th July 2012) - Khalid, Fatima; Hassan, Syed; Qureshi, Sophia; Qureshi, Waqas; Amer, Syed
Abstract : Erythromelalgia is a rare disorder frequently associated with myeloproliferative disorders. We describe a case of elderly patient diagnosed with myeloproliferative disorder in remission. The patient was on aspirin for secondary prevention of stroke and was taken off aspirin and developed erythromelalgia within two weeks of withdrawal of aspirin. After restarting aspirin, patient's symptoms improved within 2 weeks.